Almond growing in Bursa vicinity - Barut E. (XI GREMPA Seminar on Pistachios and Almonds, 2001)
In Turkey, Marmara Region's total almond production is 1315 tons. The total almond production of Bursa vicinity is about 214 tons. This production is ensured from about 37,345 almond trees in Bursa. In recent years the almond orchards have increased rapidly because of suitable ecological conditions. The important almond cultivars grown in Bursa are Nonpareil, Texas, Ne Plus Ultra, Drake and Tuono. In Bursa, about 10,000 grafted almond seedlings per year are propagated and all of them are produced in private sectors.
11. GREMPA Seminar on Pistachios and Almonds, 1999/09/01-04, Sanliurfa (Turkey)